HUBUNGAN KARAKTERISTIK IBU HAMIL DENGAN KLASIFIKASI PRE EKLAMSIA DI BEKASI - Sion Gloria Pardede; Justina Purwarini; Sada Rasmada (Jurnal Ilmiah Keperawatan, 2021)
Pre-eclampsia is a collection of symptoms such as hypertension, edema and proteinuria in pregnant, childbirth and postpartum women that occur at 20 weeks of gestation until the end of the first week after delivery. Pre-eclampsia can adversely affect the mother and fetus, such as fetal distress and even death due to lack of oxygenation. Maternal mortality rate (MMR) which occurs where one of the causes is pre-eclampsia. This study aims to determine the relationship between the characteristics of pregnant women (maternal age, parity, education, occupation and history of hypertension) to the classification of pre-eclampsia. Quantitative descriptive research design, with a total sampling of 73 pregnant women patient respondents at the East Bekasi Private Hospital in 2018-2019 who experienced pre-eclampsia. It was found that the results of the classification of respondents were mostly mild pre-eclampsia. The analysis used chi square with the conclusion that there is a relationship between the age of pregnant women and the classification of pre-eclampsia (P value 0.000), parity (P value 0.023), history of hypertension (P value 0.000). There is no relationship between education (P value 0.667) and work (P value 0.624). This research is expected to be a reference in order to improve service to patients, especially in conducting assessments on pregnant women. Where maternal age, parity and history of hypertension have a relationship with the classification of preeclmasia in pregnant women.